Post-stroke experiences and health information needs among Chinese elderly ischemic stroke survivors in the internet environment: a qualitative study - Hu, Yufan; Qiu, Xichenhui; Ji, Cuiling; Wang, Fang; He, Manlan; He, Lei; Chen, Lu (Frontiers in Psychology, 2023)
Background: Elderly stroke survivors are encouraged to receive appropriate health information to prevent recurrences. After discharge, older patients seek health information in everyday contexts, examining aspects that facilitate or impair healthy behavior.To explore the experiences of older stroke patients when searching for health information, focusing on search methods, identification of health information, and difficulties faced during the search process.Methods: Using the qualitative descriptive methodology, semi-structured interviews were conducted with fifteen participants.Results: Participants associated the health information they sought with concerns about future life prospects triggered by perceived intrusive changes in their living conditions. Based on the participants' descriptions, four themes were refined: participants' motivation to engage in health information acquisition behavior, basic patterns of health information search, source preferences for health information, and difficulties and obstacles in health information search, and two search motivation subthemes, two search pattern subthemes, four search pathway subthemes, and four search difficulty subthemes were further refined.Older stroke patients face significant challenges in searching for health information online. Healthcare professionals should assess survivors' health information-seeking skills, develop training programs, provide multichannel online access to health resources, and promote secondary prevention for patients by improving survivors' health behaviors and self-efficacy.